Assessment of Integrated Child Development Services Scheme in Select Districts of Uttarakhand - Kranthi Kumar Reddy Navuluri; Surekha Kishore; Smita Sinha; Yogesh Bahurupi; Pradeep Aggarwal; Bhavana Jain (Medsci Publications, 2020)
Introduction: ICDS scheme was launched on October 2nd 1975 to address high infant mortality, malnourishment and poor learning outcomes. Since its inception was playing  its role effectively, but still there were some shortcomings which were needed to be addressed. Uttarakhand was one among the states with poor health indicators with respect to child and mother, there is need to search for reasons effecting the implementation of programs intended for woman and child development. The present study aims to asses functioning of ICDS scheme in select Uttarakhand. Methodology: A cross sectional study was conducted selected areas of Uttarakhand state during October 2018 to June 2019, among 16 anganwadi centers from urban and rural areas of Dehradun and Haridwar districts. Results were expressed in percentages and proportions with 95% confidence interval. Relevant statistical tested applied wherever necessary. Results: Functioning of ICDS scheme in Uttarakhand varied for different services provided under it. Supplementary nutrition service was uninterrupted but medicine kits and referral slips were not supplied to anganwadi centers at the time of study. Conclusions: Study identified various insufficiencies regarding the functioning of ICDS scheme. There is a need to improve facilities at anganwadi centers for proper implementation of ICDS scheme.